Fine particulate matter and ovarian health: A review of emerging risks - Qingqing Tao; Zhengyang Zhao; Rui Yang; Qin Li; Jie Qiao (Heliyon)
Fine particulate matter (PM2.5) pollution has raised significant public concerns, especially for vulnerable populations. Studies have indicated the association between PM2.5 and ovarian disorders, although the mechanisms underlying the effects have not yet been fully elucidated. In this review, we elucidated three main conditions pertaining to ovarian function that may result from exposure to PM2.5: diminished ovarian reserve, polycystic ovary syndrome, and infertility. Specific effects of ovarian disorders caused by PM2.5 are discussed, including reactive oxygen species, apoptosis, DNA damage, and inflammation.